Trapezoidal fractures: Overview and introduction of a novel diagnostic classification system. Issue 11 (November 2020) - Safran, Tyler; Hazan, Jessica; Viezel-Mathieu, Alex; Azzi, Alain; Boily, Mathieu; Thibaudeau, Stephanie
Summary: Introduction: Trapezoidal fractures account for only 0.4% of all carpal bone fractures. Owing to their rarity, there is paucity in the literature regarding the clinical findings and treatment. This paper aims to summarize the current understanding of trapezoidal fractures and present a novel classification algorithm. Methods: A diagnostic classification algorithm was created based on the known blood supply and ligamentous attachment of the trapezoid. The proposed treatment algorithm was then applied to trapezoidal fractures in the literature to validate the algorithm and determine whether patients received treatment that was in accordance. Results: A total of 19 articles, representing 22 trapezoidal fractures were included, with two additional cases presented by the authors. Presenting symptoms were pain ( n = 21) and swelling ( n = 12). Diagnosis was made on CT in a majority of the time, 79.2% ( n = 18). All outcomes were favorable with symptomatic resolution and full range of motion after treatment, except in four patients that had co-existing wrist injuries. When the algorithm was applied, 89.5% ( n = 17) of the patients received treatment in accordance with the proposed algorithm and demonstrated good outcomes. In the remaining patients ( n = 2) whose treatment differed, one had diminished grip strength and the other was lost to follow-up. Conclusions: Given a degree of clinical suspicion including a history of blunt trauma to the hand and persisting pain, trapezoidal fractures should remain on the differential when plain radiographs fail to identify any fracture. Operative treatment is suggested if there is any significant displacement, compromise of the dorsal surface, or breech of the trapezoidal ligaments causing possible dislocation. Level of Evidence: IV – Diagnostic.